PENERAPAN STRATEGI INKUIRI DALAM MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS IV PADA MATA PELAJARAN AQIDAH AKHLAK DI SEKOLAH MIS YASIN ROKA - Trimansyah, Trimansyah; Sa’adiah, Halimatus (Prodi PGMI STIT Sunan Giri Bima, 2022)
This research is to find out the application of inquiry strategies in increasing student learning activeness in the Aqidah Akhlak subject, this research uses a type of action research using cycle stages as material for consideration of achieving maximum results with a qualitative approach. The results of the study showed that students were more enthusiastic and active when discussing, students were more focused on listening to other groups' presentations, then were not shy anymore in asking questions, wanted to fully participate in the learning that was carried out, then there was an increase in student learning activity, this could be seen from a very active learning atmosphere and lively atmosphere of discussion in class, and students are more fun in learning than as usual before.